Fabrication of dielectric elastomers with improved electromechanical properties using silicone rubber and walnut polyphenols modified dielectric particles. (July 2020) - Jiang, Liang; Wang, Yuhao; Wen, Shipeng; Zhou, Yanfen; Ma, Jianwei; Chen, Shaojuan; Jerrams, Stephen
Abstract: In this work, polyphenolic extract from walnut green husks (denoted as walnut polyphenols), which is an abundant agroindustrial residue/waste, was used to modify barium titanate (BT) particles in the preparation of silicone rubber (SR) based dielectric elastomer (DE) composites with enhanced electromechanical performance. By employing walnut polyphenols modification, the dispersibility of BT particles in the SR matrix and the compatibility between BT and SR were greatly improved, which resulted in enhanced mechanical performance of the DE composites. Dielectric property measurement showed that DE composites containing walnut polyphenols modified BT particles (WNBT) had higher dielectric constants and lower dielectric losses than that of DEs with unmodified BT particles. Furthermore, it was found that the walnut polyphenols modification resulted in decreased dielectric loss tangent of the DE composites, suggesting an improved compatibility between the modified BT particles and SR. Finally, the static and dynamic electromechanical performance of the DE composites were evaluated. The SR/5% WNBT composite achieved the highest actuated area strain of 38% among the SR based composites used in this work. Moreover, the actuated area strain of SR/WNBT composites exhibited excellent electromechanical stability during the application of cyclic voltage signals. Graphical abstract: Unlabelled Image Highlights: Walnut polyphenols extracted from walnut husks were used to modify barium titanate (BT) particles. The dispersibility of BT in silicone rubber (SR) and the compatibility between BT and SR was improved after modification. The SR/WNBT composites achieved the highest actuated area strain of 38%. The actuated area strain of SR/WNBT composites exhibited excellent stability during 50 cyclic voltage signals.